2008
DOI: 10.1002/ange.200803904
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Transient Infrared Study of the Ultrafast Deactivation Processes of Electronically Excited B‐DNA and Z‐DNA Forms of [poly(dG‐dC)]2

Abstract: Scheme 1. a) Watson-Crick G-C base pairing, b) and c) tautomeric products, d) proton transfer, e) charge transfer, and f) 1 n N p* form for the excited state of [poly(dG-dC)] 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Interestingly, the IR bleach signals reported by George and coworkers decay more slowly than our UV bleach signals (compare Figures S2 and S3 of ref. [25] with Figure 1 b). This is largely due to the different solvent conditions: our experiments were carried out in H 2 O, while those of George and coworkers were carried out in D 2 O.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, the IR bleach signals reported by George and coworkers decay more slowly than our UV bleach signals (compare Figures S2 and S3 of ref. [25] with Figure 1 b). This is largely due to the different solvent conditions: our experiments were carried out in H 2 O, while those of George and coworkers were carried out in D 2 O.…”
mentioning
confidence: 84%
“…George and coworkers studied transient changes to the vibrational spectra of the B-and Z-forms of the closely related homoduplex of polyA C H T U N G T R E N N U N G (dGdC) in D 2 O by using the picosecond time-resolved infrared (ps-TRIR) technique with UV excitation at 267 nm. [24,25] The researchers reported that the vibrational bleach signals of the B-form duplex decay biexponentially whereas the Z-form bleach signals exhibit monoexponential dynamics. Despite this reported difference, inspection of the decay curves suggests that the overall decays for the B-and Zforms are similar, in agreement with our results.…”
mentioning
confidence: 99%
“…Transient vibrational spectroscopy provides a powerful solution-phase structural tool to characterize the various intermediates via an infrared fingerprint of excited state intermediates of mononucleotides, dinucleotides and polymeric systems. [10][11][12][13] In this paper we investigate the origins of the long-lived excited state present in UV excited alternating A-T systems by studying the dApT dinucleotide using ps-TRIR, FTIR In solution the dinucleotide dApT exists in equilibrium between two structures, a stacked and unstacked form, viz; (dApT)S ⇋ (dApT)U, see Figure 1. 1 H NMR in buffered D2O indicates that dApT is 38% stacked and 62% unstacked [see Table S1 in supporting information SI].…”
mentioning
confidence: 99%
“…Although the details of photoreactivity of nucleic acids is a matter of intense debate, all studies indicate that internal conversion of electronic energy into vibrational energy is a fast process, 6,9,10,55 and that the ground state recovery is on the picosecond time scale to several nanoseconds for GC rich duplex 5,8 . With the reasonable assumption that similar decay processes are at stake in our structures in the gas phase, it means that electron photodetachment is competitive with internal vibrational relaxation, and occurs very rapidly after electronic excitation.…”
Section: Influence Of Structure On the Photoreactivity Of Isolated Dnmentioning
confidence: 99%
“…In solution, Watson-Crick double helices have short excited states lifetime (depending on the detection wavelength from several picoseconds 5,6 to nanoseconds for GC-rich double helix 7,8 ), which explain the relative stability of the DNA against UV radiation. Conformational motions of the DNA strands and the solvent modulate the lifetime of the excited states [9][10][11] Despite all of these information, the nature and the relaxation of the excited states of nucleic acids are still a matter of debate. UV spectroscopy could be used to probe the higher-order structure of nucleic acid complexes produced by soft ionization mass spectrometry and understand intrinsic effects of structuration on optical properties.…”
Section: Introductionmentioning
confidence: 99%